2021
DOI: 10.3390/molecules26051412
|View full text |Cite
|
Sign up to set email alerts
|

Precise Synthesis and Thin Film Self-Assembly of PLLA-b-PS Bottlebrush Block Copolymers

Abstract: The ability of bottlebrush block copolymers (BBCPs) to self-assemble into ordered large periodic structures could greatly expand the scope of photonic and membrane technologies. In this paper, we describe a two-step synthesis of poly(l-lactide)-b-polystyrene (PLLA-b-PS) BBCPs and their rapid thin-film self-assembly. PLLA chains were grown from exo-5-norbornene-2-methanol via ring-opening polymerization (ROP) of l-lactide to produce norbornene-terminated PLLA. Norbonene-terminated PS was prepared using anionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Morphological changes for PS 17 - b -PDMH films were observed as f PDMH increased from about 0.58 to about 0.73, influencing the molecular packing shapes and interfacial curvatures (Figure B top and middle rows and Figures S6A and S7A). Other researchers have demonstrated that BBCPs can phase-separate into lamellar, cylindrical, or spherical morphologies, which are dependent upon the block compositions and polymer side-chain lengths. , Our BBCP films appeared to show lamellar and cylindrical morphologies for the films with f PDMH values of 0.58 and 0.73, respectively; however, definitive assignments require future scattering experiments . Due to nonselective CHCl 3 used to cast the films and no preferential interfacial interaction between the individual block and glass surface, the self-assembled orientation exhibited perpendicular features to the surfaces. , This indicates that a balance exists between the interaction of the sterically hindered polymer brushes and the surface or the air interfaces .…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Morphological changes for PS 17 - b -PDMH films were observed as f PDMH increased from about 0.58 to about 0.73, influencing the molecular packing shapes and interfacial curvatures (Figure B top and middle rows and Figures S6A and S7A). Other researchers have demonstrated that BBCPs can phase-separate into lamellar, cylindrical, or spherical morphologies, which are dependent upon the block compositions and polymer side-chain lengths. , Our BBCP films appeared to show lamellar and cylindrical morphologies for the films with f PDMH values of 0.58 and 0.73, respectively; however, definitive assignments require future scattering experiments . Due to nonselective CHCl 3 used to cast the films and no preferential interfacial interaction between the individual block and glass surface, the self-assembled orientation exhibited perpendicular features to the surfaces. , This indicates that a balance exists between the interaction of the sterically hindered polymer brushes and the surface or the air interfaces .…”
Section: Resultsmentioning
confidence: 61%
“…13,37 Our BBCP films appeared to show lamellar and cylindrical morphologies for the films with f PDMH values of 0.58 and 0.73, respectively; however, definitive assignments require future scattering experiments. 38 Due to nonselective CHCl 3 used to cast the films and no preferential interfacial interaction between the individual block and glass surface, the self-assembled orientation exhibited perpendicular features to the surfaces. 26,39 This indicates that a balance exists between the interaction of the sterically hindered polymer brushes and the surface or the air interfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the diblock copolymers, the T g values of PS and P2VP blocks cannot be observed, indicating that the PS/P2VP (amorphous blocks) and PLLA/PDLA (crystalline blocks) are miscible in the melt [50,51]. The PLLA/PDLA crystallites are well organized (as proved by the distinct ∆H m ) and limit the mobility of the amorphous blocks [50]. In addition, for PS 6.2 -b-PDLA 7.1 (Figure 4c), the T g of PS overlaps with the exothermic peaks from the cold-crystallization temperature (T cc ) of PLA.…”
Section: Resultsmentioning
confidence: 96%
“…The T g values of the amorphous PS 6.2 -OH and P2VP 5.2 -OH precursors are observed to be 92.3 • C and 93.6 • C (Table 2), respectively. In the case of the diblock copolymers, the T g values of PS and P2VP blocks cannot be observed, indicating that the PS/P2VP (amorphous blocks) and PLLA/PDLA (crystalline blocks) are miscible in the melt [50,51]. The PLLA/PDLA crystallites are well organized (as proved by the distinct ∆H m ) and limit the mobility of the amorphous blocks [50].…”
Section: Resultsmentioning
confidence: 97%